Creative Drama: A Tool for Reducing Teenage Pregnancy in Calabar Metropolis - OGAR , Helen Kingsley; YTA, Edisua Merab (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This research addresses the pervasive issue of teenage pregnancy, a critical concern in the realm of reproductive health that has drawn international attention. Focused on the Calabar Metropolis, the study aims to evaluate the efficacy of creative drama as a proactive tool in mitigating teenage pregnancy rates. The primary objective is to address and rectify the prevailing sexual attitudes among teenagers, which often lead to unintended consequences such as unwanted pregnancies, premature childbirth, abandonment of infants in distressing locations, abortions, school dropouts, and the heightened risk of sexually transmitted diseases (STDs), including HIV/AIDS. Employing experimental and survey methodologies, the study utilised drama, narratology, and questionnaires as instruments, subjecting the gathered data to scientific analysis. Educational institutions, namely the University of Calabar Staff School, Obufa Esuk Orok Primary School, and Inih Andem Nursery School in Calabar, were selected for a comprehensive assessment of the potential impact of creative drama on reducing teenage pregnancy. Key findings underscored that creative drama significantly influences teenagers' attitudes towards premarital sex, with a majority expressing a negative stance on engaging in such behavior. Respondents emphasised the importance of waiting until after marriage for sexual activity and acknowledged creative drama's effectiveness in curbing teenage pregnancy. The study concludes that the adoption of creative drama as an educational tool yields positive outcomes, recommending that parents play an active role in providing both emotional and material support to their daughters. Additionally, it suggests implementing creative drama in schools for educational purposes and advocates for further research on various aspects of reproductive health concerns related to teenagers.